2021
DOI: 10.1111/pbi.13612
|View full text |Cite
|
Sign up to set email alerts
|

The rice RNase P protein subunit Rpp30 confers broad‐spectrum resistance to fungal and bacterial pathogens

Abstract: RNase P functions either as a catalytic ribonucleoprotein (RNP) or as an RNA-free polypeptide to catalyse RNA processing, primarily tRNA 5 0 maturation. To the growing evidence of noncanonical roles for RNase P RNP subunits including regulation of chromatin structure and function, we add here a role for the rice RNase P Rpp30 in innate immunity. This protein (encoded by LOC_Os11g01074) was uncovered as the top hit in yeast two-hybrid assays performed with the rice histone deacetylase HDT701 as bait. We showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…To confer a broad-spectrum and a durable resistance in this cereal plant, currently, the best way forward is to select among the inherent resistance genes of rice to breed disease-resistant cultivars. In this respect, many discoveries have been made recently, such as the RNase P protein subunit Rpp30 with tRNA processing (Li W. et al, 2021), executor R proteins' (Xa7 and Xa23 with EBE Avrxa23 ) response to T3Es of pathogens Wei et al, 2021), and Bacterial Leaf Streak 1 (Ma Z. et al, 2021) which encodes a protein that acts against different pathogenic strains (Chen F. et al, 2021). As another economically important crop, wheat is susceptible to Fusarium head blight (Fhb) that is caused by several Fusarium strains.…”
Section: Pathogenesismentioning
confidence: 99%
“…To confer a broad-spectrum and a durable resistance in this cereal plant, currently, the best way forward is to select among the inherent resistance genes of rice to breed disease-resistant cultivars. In this respect, many discoveries have been made recently, such as the RNase P protein subunit Rpp30 with tRNA processing (Li W. et al, 2021), executor R proteins' (Xa7 and Xa23 with EBE Avrxa23 ) response to T3Es of pathogens Wei et al, 2021), and Bacterial Leaf Streak 1 (Ma Z. et al, 2021) which encodes a protein that acts against different pathogenic strains (Chen F. et al, 2021). As another economically important crop, wheat is susceptible to Fusarium head blight (Fhb) that is caused by several Fusarium strains.…”
Section: Pathogenesismentioning
confidence: 99%
“…In wheat, the HAT complex TaGCN5-TaADA2 plays a role in the regulation of cuticular wax biosynthesis in response to powdery mildew [113]. In rice, C-terminal tail binding of subunit OsRpp30 to the HDAC OsHDT701 causes a negative defense response to the fungal and bacterial pathogens Magnaporthe oryzae and Xanthomonas oryzae, respectively [114]. Tomato plant resistance to bacterial wilt (Ralstonia solanacearum) in two different cultivars showed that differential HDAC expression led to the downregulation of resistant genes [115].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…For instance, wheat HAT complex TaGCN5-TaADA2 activates wheat wax biosynthesis by mediating histone acetylation at the promoters of biosynthesis-related genes, thereby providing wax signals for the conidial germination of fungal pathogen Bgt (Table 1, Kong et al, 2020b). Rice HDAC OsHDT701 interacts with the rice RNase P subunit Rpp30 and negatively regulates rice defense responses to the fungal pathogen Magnaporthe oryzae (M. oryzae) and bacterial pathogen Xoo by mediating histone deacetylation at PRR and defense genes (Table 1, Ding et al, 2012;Li et al, 2021). Similarly, wheat HDAC TaHDA6, the ortholog of Arabidopsis AtHDA6, could function in concert with WD40-repeat protein TaHOS15 and another HDAC TaHDT701 to suppress wheat defense responses to the fungal pathogen Bgt by reducing levels of histone acetylation at defense-related genes (Table 1, Liu et al, 2019;Zhi et al, 2020).…”
Section: Tachr729mentioning
confidence: 99%